A Literature Review: The Effect of Giving Lavender Aromatherapy On Sleep Quality In The Elderly - Achmad Dwi Kurniawan; Imam sunarno; Muhammad Miftachul Ulum (Universitas Islam Balitar, 2022)
Elderly is the final stage of the development of the human life cycle, aging is generally defined as a progressive physiological decline after the reproductive stage of life. Common health problems in the elderly are sleep disturbances. Sleep disorders or insomnia is a condition of a person who does not get enough sleep at night, wakes up at night, or wakes up too early. The purpose of the literature review: to study the effect of using lavender aromatherapy on sleep quality in the elderly. The method used is a traditional review with the samples being accredited national and international journals. With inclusion criteria, national and international journals from different databases were selected independently by the researcher. The results: the use of lavender aromatherapy improves sleep quality in the elderly, with p value = 0.000. Improved sleep quality occurs by giving essential oils every night for 7 consecutive days. Conclusion: the use of lavender aromatherapy can be used to improve sleep quality in the elderly. Suggestion: for the elderly who have sleep disorders, you can use 5-6 drops of lavender aromatherapy oil on their pillows every night before going to bed.